PEMODELAN PROSEDUR KARANTINA PENDATANG DALAM RANGKA PENCEGAHAN COVID-19 DI KOTA TARAKAN MENGGUNAKAN PETRI NET - Murdianto, Deny; Santoso, Hadi (PATTIMURA UNIVERSITY, 2020)
In ordered to prevent the transmission of Covid-19, the government of Tarakan city quarantines immigrants who entered Tarakan city. The government of Tarakan city have created a procedure for implementing the quarantine. Based on these procedures, this article aims to model the quarantine procedure using a Petri net. The Petri net model of the quarantine procedure for immigrants in the context of preventing Covid-19 in Tarakan City consists of eighteen transitions and sixteen places. The evolution of circumstances indicated by the matrix analyzed against the quarantine procedure for domestic immigrants with the final destination of Tarakan city. The determination of marking must be determined seriously so that this quarantine procedure can run smoothly according to purpose. The number of officers must be carefully taken into account so that there is no accumulation of queues of immigrants who was carry out the inspection. The capacity of quarantine places and hospitals must also be well prepared so that they are always available and ready to accept immigrants who was be quarantined.